Long Sleep Duration Associated With Cognitive Impairment in Chinese Community-Dwelling Older Adults. Issue 12 (December 2021) - Zhang, Hui; Ma, Weibo; Chen, Yaoxin; Wang, Feng; Wang, Jingru; Han, Peipei; Wang, Yiwen; Zhang, Chenyu; Xie, Fandi; Niu, Shumeng; Hu, Hao; Wang, Hong; et al.
Abstract: We aimed to examine the association between sleep duration and impaired cognitive function in different cognitive domains in Chinese community-dwelling older adults. A total of 1591 participants (≥60 years) were divided into five groups: ≤6 hours (very short sleep duration), >6 to 7 hours (short sleep duration), ≥7 to 8 hours (moderate sleep duration), >8 to 9 hours (moderately long sleep duration), and >9 hours (long sleep duration), according to sleep duration. Cognitive function was assessed using the Mini-Mental State Examination. Long sleep duration significantly increased the likelihood of cognitive impairment. In addition to attention, long sleep duration was negatively related to poorer global cognition and other cognitive domain functions. With the stratification of age groups, long sleep duration was negatively associated with other cognitive domain functions except delayed recall in older elderly (≥75 years) people, but not in younger elderly (60–74 years) people. Long sleep duration was associated with higher rates of cognitive impairment, poorer global cognition, and declined orientation, memory, language ability, and executive function in Chinese community-dwelling older adults, which was more significant in older elderly people.